Daily Radiation Budget of the Baltic Sea Surface from Satellite Data - Zapadka Tomasz; Krężel Adam; Paszkuta Marcin; Darecki Mirosław (Polish Maritime Research, 2015)
Recently developed system for assessment of radiation budget for the Baltic Sea has been presented and verified. The system utilizes data from various sources: satellite, model and in situ measurements. It has been developed within the SatBałtyk project (Satellite Monitoring of the Baltic Sea Environment - www.satbaltyk.eu) where the energy radiation budget is one of the key element. The SatBałtyk system generates daily maps of the all components of radiation budget on every day basis. We show the scheme of making daily maps, applied algorithms and empirical data collection within the system. An empirical verification of the system has been carried out based on empirical data collected on the oil rig placed on the Baltic Sea. This verification concerned all the components of the surface radiation budget. The average daily NET products are estimated with statistical error ca. 13 Wm-2. The biggest absolute statistical error is for LWd component and equals 14 Wm-2. The relative error in relation to the average annual values for whole Baltic is the biggest for SWu and reaches 25%. All estimated components have correlation coefficient above 0.91.